Primary Fallopian Tube Carcinoma Discovered as an Incidental Finding - A Case Report - Singh, Mrinalini; Das, Sanjay; Shaukin, Shilpi (Medical Journal of Shree Birendra Hospital, 2018)
Introduction: Primary malignant tumour of fallopian tube is very rare. The reported incidence of tumour varies from 0.1 to 1.8% of all gynaecological cancers. There is no specific clinical feature and therefore the disease is often misdiagnosed as ovarian neoplasm or other gynaecological tumours. A preoperative diagnosis even by radiological assay is many times difficult because the features are similar to ovarian neoplasm, tubo-ovarian abscess or hydrosalpinx. We report a case of 45 years old female who presented with multiple episodes of pervaginum bleeding since past one year and was diagnosed as primary fallopian tube carcinoma on histopathology examination.